Analysis by Real-Time Pcr of Five Transport and Conservation Mediums of Nasopharyngeal Swab Samples to Covid-19 Diagnosis in Santiago of Chile - Sandino-Garcia, A; Imarai-Bahamonde, C; Acuna-Castillo, C; Valdes-Henriquez, D; Milla-Brito, L; Vargas-Valenzuela, D; Negrete-Vergara, C; Negrete-Vergara, C; Luraschi-Vargas, R; Mena-Silva, J; Barrera-Ávalos, C; Reyes-Lopez, F; et al. (John Wiley and Sons Inc, 2022)
Due to the COVID-19 pandemic, many transport kits have been manufactured to preserve and transport nasopharyngeal swab samples (NPSs) from patients. However, there is no information on the performance of the different virus transport media (VTM) used in COVID-19 diagnosis in the population of Santiago de Chile. We compared the RT-qPCR amplification profile of five different viral transport kit mediums, including DNA/RNA Shield™, NAT, VTM-N, Ezmedlab™, and phosphate-buffered saline (PBS), for NPSs from Central Metropolitan Health Service, Santiago, Chile. The DNA/RNA Shield™ medium showed a better performance in terms of Cq and RFU values for the internal reference RNase P and viral ORF1ab probes. By contrast, the PBS transport medium registered higher Cq values for the viral and reference gene, compared to the other VTM. DNA/RNA Shield™ shows higher relative fluorescence units (RFUs) and lower Cq values for the reference gene. Collectively, our results suggest that the PBS medium could compromise the sample diagnosis because of its lower RT-qPCR performance. The NAT, Ezmedlab and VTM-N, and DNA/RNA Shield™ media show acceptable RT-qPCR parameters and, consequently, seem suitable for use in COVID-19 diagnosis. © 2021 Wiley Periodicals LLC